Pharmacovigilance of triazole antifungal agents: Analysis of the FDA adverse event reporting system (FAERS) database - Zhou, Jianxing; Wei, Zipeng; Xu, Baohua; Liu, Maobai; Xu, Ruichao; Wu, Xuemei (Frontiers in Pharmacology, 2022)
Introduction: Triazole antifungal drugs (TAD) are widely used to treat invasive fungal infections due to their broad antifungal spectrum and low toxicity. Despite their preference in the clinic, multiple Adverse Events (AE) are still reported each year. Objective: We aimed to characterize the distribution of AEs associated with TAD in different systems and to identify Important Medical Events (IME) signals for TAD. Methods: The U.S. Food and Drug Administration Adverse Event Reporting System (FAERS) was queried for AEs related to TAD from 2012 to 2022. The AEs caused by all other drugs and non-TAD antifungal drugs were analyzed as references. Reporting odds ratio and Bayesian confidence propagation neural network of information components were used to evaluate the association between TAD and IME. Visual signal spectrum is mapped to identify potential adverse reaction signals. Results: Overall, 10,262 AEs were reported to be associated with TAD, of which 5,563 cases were defined as IMEs. Common adverse drug reactions (ADR) mentioned in the instructions such as delirium and hypokalemia were detected, as well as unlabeled ADRs such as rhabdomyolysis and hepatitis fulminant. cholestasis, drug-induced liver injury, QT interval prolongation and renal impairment have notable signals in all TADs, with 50 percent of patients developing a severe clinical outcome. Isavuconazole had the lowest signal intensity and demonstrated a superior safety profile. Conclusion: Most results are generally consistent with previous studies and are documented in the prescribing instructions, but some IMEs are not included, such as hepatitis fulminant. Additional pharmaco-epidemiological or experimental studies are required to validate the small number of unlabeled ADRs. TAD-related IMEs have a considerable potential to cause clinically serious outcomes. Clinical use of TAD requires more attention.